Implementasi Pembelajaran Berdiferensiasi Berbasis Joyful Learning dalam Mengatasi Perbedaan Kecepatan Belajar Siswa pada Mata Pelajaran Matematika - Vettris Dwarti Sinaga; Shintia Ariany Siahaan; Shindy Balerina Situmorang; Venny Flora Cita Manurung; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to describe and analyze the implementation of differentiated instruction based on joyful learning in mathematics to address differences in students’ learning speeds at SD Negeri 066053 Medan Denai. The background of this study is based on the fact that variations in students’ abilities and learning speeds are often not optimally accommodated in conventional instruction. The research method used is a qualitative approach with a descriptive research design. Data collection techniques were conducted through observation, interviews, and documentation. The results of the study indicate that the application of differentiated instruction combined with the joyful learning approach can create a pleasant learning atmosphere, enhance students’ learning motivation, and provide students with the opportunity to learn according to their readiness level and learning interests. Furthermore, this strategy has proven effective in helping students with varying learning paces to still achieve learning objectives optimally. Overall, the implementation of differentiated instruction based on the joyful learning approach serves as an innovative solution for improving the quality of mathematics education in elementary schools.